2021
DOI: 10.3389/fncel.2021.663384
|View full text |Cite
|
Sign up to set email alerts
|

HDAC4 Knockdown Alleviates Denervation-Induced Muscle Atrophy by Inhibiting Myogenin-Dependent Atrogene Activation

Abstract: Denervation can activate the catabolic pathway in skeletal muscle and lead to progressive skeletal muscle atrophy. At present, there is no effective treatment for muscle atrophy. Histone deacetylase 4 (HDAC4) has recently been found to be closely related to muscle atrophy, but the underlying mechanism of HDAC4 in denervation-induced muscle atrophy have not been described clearly yet. In this study, we found that the expression of HDAC4 increased significantly in denervated skeletal muscle. HDAC4 inhibition can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…In addition to its role in the occurrence, progression and treatment of cancer, CDKN1A has also been proved to be related to muscle atrophy. Wenjing Ma et al found that CDKN1A was upregulated in denervated skeletal muscle (30). The increase of CDKN1A expression level can also be found in the muscle atrophy model induced by starvation (31).Similarly, the expression of CDKN1A increased in the model of muscle atrophy induced by hindlimb suspension, but decreased after reloading (32).…”
Section: Discussionmentioning
confidence: 96%
“…In addition to its role in the occurrence, progression and treatment of cancer, CDKN1A has also been proved to be related to muscle atrophy. Wenjing Ma et al found that CDKN1A was upregulated in denervated skeletal muscle (30). The increase of CDKN1A expression level can also be found in the muscle atrophy model induced by starvation (31).Similarly, the expression of CDKN1A increased in the model of muscle atrophy induced by hindlimb suspension, but decreased after reloading (32).…”
Section: Discussionmentioning
confidence: 96%
“…In addition to atrogin-1 and MuRF1 overexpression, an increase in muscle HDAC4 and myogenin has been recently reported in sepsis ( 76 ), and in other conditions that induce muscle atrophy such as neurological disease ( 77 ), disuse ( 78 ) and aging ( 53 ). Furthermore, HDAC4 inhibition is reported to decrease denervation-induced muscle atrophy through decreased expression of muscle specific E3 ubiquitin ligases atrogin-1 and MuRF1 and autophagy related proteins ( 79 ). In this regard, we have previously reported that the treatment with this nutraceutical was also able to prevent the activation of the HDAC4-myogenin axis and the skeletal muscle loss induced by aging in rats ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase in proteolytic activity can directly cause skeletal muscle atrophy. Previous studies have shown that skeletal muscle atrophy is accompanied by significant activation of the proteolytic UPS and ALS pathways [ 13 , 14 ]. Moreover, oxidative stress and inflammation can trigger proteolysis by activating the UPS and ALS pathways [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Muscle ring-finger 1 (MuRF1) and muscle atrophy F-box (MAFbx) are two muscle-specific ubiquitin E3 ligases that are most essential to the UPS. They are highly expressed in a variety of muscle atrophy models [ 13 , 14 , 15 , 16 ]. Autophagy-related proteins, PINK1, BNIP3, LC3B, and ATG7, are key effectors of the ALS and also play an important role in the process of muscle atrophy.…”
Section: Introductionmentioning
confidence: 99%